PLANNING MODEL TOTAL REQUIREMENTS OFFICER PERSONNEL FOR SUPPORTING THE NAVAL TASKS - Dian Muhtar Budiasa; Budisantoso Wirjodirdjo; Ahmadi Ahmadi; Mukhlis Mukhlis (JOURNAL ASRO, 2022)
As the main component of the defense and security of the maritime dimension of the state, the Indonesian Navy must be able to carry out organizational tasks effectively and efficiently so that the success of achieving organizational goals can be achieved. The main resource needed to support the implementation of the tasks of the Indonesian Navy is Human Resources or personnel. With an important role as leader/superior in decision-making and policy-making as well as the organizational driving force, officer personnel planning is urgently needed in manning the entire spectrum of office space assignments in a timely, quality, quantity, and place manner. This planning is a form of implementation within the Indonesian Navy officer personnel development system with complex and dynamic system characteristics. Given these system characteristics, the researcher uses a system thinking approach analysis with the aim of articulating the problem in the form of a causal loop diagram model and then integrating it into a dynamic system simulation model with the aim of obtaining the best policy scenario formulation from the simulation results of the planning model for the number of officer personnel needs at rank strata. "C" to "H", so that the behavioral conditions of a stable personnel development system are still achieved regarding the elements of the number of personnel needs in supporting the continuation of the implementation of the duties of the Indonesian Navy effectively and efficiently in achieving organizational goals. Keywords: complex, dynamic, personnel coaching system, system thinking, dynamic system